Editorial special issue: Urban freight, land use planning and public administration strategies - Edoardo Marcucci; Valerio Gatta; Laetitia Dablanc (REGION, 2018)
This editorial introduces the special issue on 2Urban Freight, land use planning and public administration strategies". In the first part, it describes the rationale for the special issue and motivates the choice of focusing on land use planning and public administration strategies in the urban freight transportation context. In the second part, the editorial illustrates the specific contributions provided by the research papers included in the special issue showing the diversity of policy questions urban freight entails. It demonstrates how big is the gap between what is needed to provide a well-developed framework for fostering sustainable urban freight and what is actually known.
Keywords: 330